Targeting the lung endothelial niche to promote angiogenesis and regeneration: A review of applications - Tsikis, Savas T.; Hirsch, Thomas I.; Fligor, Scott C.; Quigley, Mikayla; Puder, Mark (Frontiers in Molecular Biosciences, 2022)
Lung endothelial cells (ECs) comprise the pulmonary vascular bed and account for the majority of cells in the lungs. Beyond their role in gas exchange, lung ECs form a specialized microenvironment, or niche, with important roles in health and disease. In early development, progenitor ECs direct alveolar development through angiogenesis. Following birth, lung ECs are thought to maintain their regenerative capacity despite the aging process. As such, harnessing the power of the EC niche, specifically to promote angiogenesis and alveolar regeneration has potential clinical applications. Here, we focus on translational research with applications related to developmental lung diseases including pulmonary hypoplasia and bronchopulmonary dysplasia. An overview of studies examining the role of ECs in lung regeneration following acute lung injury is also provided. These diseases are all characterized by significant morbidity and mortality with limited existing therapeutics, affecting both young children and adults.